2014
DOI: 10.1007/s00424-014-1618-8
|View full text |Cite
|
Sign up to set email alerts
|

The cystic fibrosis transmembrane conductance regulator is an extracellular chloride sensor

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a Cl− channel that governs the quantity and composition of epithelial secretions. CFTR function is normally tightly controlled as dysregulation can lead to life-threatening diseases such as secretory diarrhoea and cystic fibrosis. CFTR activity is regulated by phosphorylation of its cytosolic regulatory (R) domain, and ATP binding and hydrolysis at two nucleotide-binding domains (NBDs). Here, we report that CFTR activity is also controlled by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Several channels and transporters regulate [Cl − ] i (Plans, Rickheit & Jentsch, 2009;Krall et al, 2015;Kunzelmann, 2015;Stauber, 2015;Oh & Jung, 2016), and conversely, changes in [Cl − ] i regulate their activity (Choi et al, 2001;Xie & Schafer, 2004;Plested, 2011;Yu et al, 2013;Broadbent et al, 2015).…”
Section: (3) Effects Of CL − On Channels and Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several channels and transporters regulate [Cl − ] i (Plans, Rickheit & Jentsch, 2009;Krall et al, 2015;Kunzelmann, 2015;Stauber, 2015;Oh & Jung, 2016), and conversely, changes in [Cl − ] i regulate their activity (Choi et al, 2001;Xie & Schafer, 2004;Plested, 2011;Yu et al, 2013;Broadbent et al, 2015).…”
Section: (3) Effects Of CL − On Channels and Receptorsmentioning
confidence: 99%
“…By mutagenesis of the CFTR, they showed that alterations in residues R347 and R334 of the channel pore might be necessary for activation of ATP efflux in response to increased [Cl − ] e (Jiang et al, 1998). Subsequently, Broadbent et al (2015) found that increased [Cl − ] e stimulates CFTR activity, and similarly proposed that CFTR may act as an [Cl − ] e sensor (Broadbent et al, 2015). This characteristic was conferred by arginine residue R899, located in extracellular loop 4 of the CFTR, linking [Cl − ] e sensing to changes in the ATP binding energy at nucleotide binding domain 1 (NBD1) that affected dimerization with NBD2 and ATP turnover (Broadbent et al, 2015).…”
Section: (3) Effects Of CL − On Channels and Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acinar Ca 2+ signals also regulate acinar fluid secretion via Ca 2+ -activated Cl − and K + channels (Petersen, 1992;Park et al 2001). However, the major component of pancreatic fluid secretion is contributed by the ducts and this is regulated by secretin-elicited intra-ductal cyclic AMP formation controlling cystic fibrosis transmembrane conductance regulator (CFTR) channels (Argent, 2006), whose openings are also regulated by the Cl − concentration in the luminal fluid (Broadbent et al 2015).…”
Section: Introductionmentioning
confidence: 99%